The Territorial and Socio-Economic Characteristics of the Digital Divide in Canada - Koch, Katharina (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2022)
The digital divide in Canada has gained significant attention from policymakers and the public in 2020 as a result of the COVID-19 pandemic. The pandemic enhances the vulnerability of residents in rural and Indigenous communities that lack high-speed Internet access which affects their residents’ ability to participate in an online work and learning environment. However, digital inequalities also remain an issue in urban settings despite the physical infrastructure that is usually in place to connect to high-speed Internet. The federal government has launched several funding initiatives at the end of 2020; however, this paper argues that the current federal policy strategy to address the digital divide is insufficient. By drawing on the intersectional character of the digital divide, which is interlinked with other types of socio-economic inequalities, this paper investigates why the federal broadband development approach remains problematic. As the digital divide in Canada persists, this paper explores current federal funding initiatives and their effectiveness in supporting broadband deployment across rural and Indigenous communities. The analysis shows inequalities regarding broadband access and funding distribution in Canada which also stem from a lack of democratic efficacy during federal hearings.